DEVELOPMENT OF CHILDREN'S CREATIVE THINKING BASED ON AN INTEGRATIVE APPROACH IN PRIMARY EDUCATION - Rasulova Sanobar Abbasovna (Western European Studies, 2024)
This article describes the components of integration, the integration approach and the advantages of the integration approach in developing the creative thinking of primery school students.
Keywords: education; upbringing; creativity